Formulasi Strategi OCBC dalam Menghadapi Daya Saing Perbankan - Jenni, Jenni; Murhadi, Werner R. (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze what strategic options a company can make so that it can survive in future situations. The key concept in this research is strategy formulation, where the quantitative method used includes industrial management steps implemented by OCBC in facing banking business competition. The results of research on the internal and external environment reveal OCBC's strengths, weaknesses, opportunities and challenges (SWOT). The SWOT analysis is then entered into several matrices, including EFE and IFE, CPM, TOWS, SPACE, BCG, IE, GSM, and QSPM. The final recommendation obtained is that OCBC's strategy choice is market penetration considering that the market share in Indonesia is still quite large.